2018
DOI: 10.1096/fj.201800059r
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles extracted from young donor serum attenuate inflammaging via partially rejuvenating aged T‐cell immunotolerance

Abstract: Biologic aging results in a chronic inflammatory condition, termed inflammaging, which establishes a risk for such age-related diseases as neurocardiovascular diseases; therefore, it is of great importance to develop rejuvenation strategies that are able to attenuate inflammaging as a means of intervention for age-related diseases. A promising rejuvenation factor that is present in young blood has been found that can make aged neurons younger; however, the component in the young blood and its mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 71 publications
0
50
0
1
Order By: Relevance
“…The results revealed that the administration of exosomes clearly inhibited caspase-1 activation, which subsequently prevented GSDMD cleavage and membrane GSMDM pore formation that leads to the secretion of inflammatory cytokines, including IL18, IL-1β, TNF-α, IL-6, and HMGB1. Previous studies have shown that coalescing young and old vessels inhibited inflammation reactions in older mice (Wang et al, 2018;Zhang and Jin, 2020), indicating that there is an anti-inflammatory effect of plasma exosomes. In contrast to cell type-specific exosomes in a highly controlled process, the diversity of plasma cells determines its functional diversity.…”
Section: Discussionmentioning
confidence: 92%
“…The results revealed that the administration of exosomes clearly inhibited caspase-1 activation, which subsequently prevented GSDMD cleavage and membrane GSMDM pore formation that leads to the secretion of inflammatory cytokines, including IL18, IL-1β, TNF-α, IL-6, and HMGB1. Previous studies have shown that coalescing young and old vessels inhibited inflammation reactions in older mice (Wang et al, 2018;Zhang and Jin, 2020), indicating that there is an anti-inflammatory effect of plasma exosomes. In contrast to cell type-specific exosomes in a highly controlled process, the diversity of plasma cells determines its functional diversity.…”
Section: Discussionmentioning
confidence: 92%
“…The autoimmune regulator (Aire) gene is expressed by mTECs to mediate self-antigen expression and to promote central immune tolerance via thymocyte negative selection and Treg generation (39,40). In the aged thymus, Aire-expressing mTECs are disrupted and/or decreased (7,29). Because transplantation of FREFs enhanced biological All of the data are from 3 independent experiments.…”
Section: Preparation and Characterization Of Frefsmentioning
confidence: 99%
“…These factors are produced from cells of mesenchymal or hematopoietic origin, but target nonhematopoietic TECs associated with upregulating FoxN1 expression in TECs. Finally, epigenetically based rejuvenation, via extracellular vesicles and exosomes extracted from young, healthy serum, has been shown to rejuvenate not only the peripheral T cell system, but also the thymus by enhancing FoxN1 expression (29). Therefore, potential exists for rejuvenating thymic aging by primarily targeting the restoration of TEC homeostasis through rescuing age-related decreased FoxN1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…(2) cytokine-to-TEC based therapy, such as keratinocyte growth factor (KGF) [116,117] and IL-22 [118][119][120]; (3) genetically-based methods (enhancement of exogenous FoxN1 expression with FoxN1 cDNA plasmid and FoxN1 transgene) [79][80][81], and (4) epigenetically-based methods (via exosomes extracted from young healthy serum) [121].…”
Section: Trends In Rejuvenation Of Age-related Thymic Atrophymentioning
confidence: 99%